Problem Pembelajaran Pendidikan Agama Kristen Dimasa Pandemi Terhadap Psikologi Anak - Darianti; Talizaro Tafonao (SANCTUM DOMINE: JURNAL TEOLOGI, 2021)
The purpose of writing this article is to find out about the various problems that occur in the learning process during the Covid-19 pandemic. This study departs from the writer's anxiety about the presence of Covid-19 in Indonesia. The author observes empirically that Covid-19 has had a major impact on the psychology of children as explained in this article. This study uses the literature method with a descriptive qualitative approach. The analysis process carried out is to use various literary sources, both journals, books and other reliable reference materials to support the author's analysis related to the problems of learning Christian religious education during the pandemic. The results found in this study were efforts, tips and strategies in overcoming various problems, especially in dealing with children's psychology when learning was taking place by cooperating with parents and teachers in applying effective learning principles according to children's needs. Thus, Christian religious education has a very significant role in overcoming these various prolems.